Entrepreneurial orientation, absorptive capacity, market orientation and technological innovation capabalities of SMEs in Kurdistan, Iraq - Al-Janabi, Abdulqadir Rahomee Ahmed (2016)
Innovation capabilities have become an important component for small and medium enterprises (SMEs) in the industrial sector to cope with intense competition and to meet customers’ needs. Due to inconsistency in the findings of previous studies on the antecedent factors that may influence these capabilities, this study intended to empirically examine the relationships between entrepreneurial orientation, absorptive capacity, market orientation, and technological innovation capabilities among the industrial SMEs in an unstable environment, and also to determine whether market orientation has a mediating role in the relationship between entrepreneurial orientation, absorptive capacity, and technological innovation capabilities . This study adopted the Resource-Based Theory as an underpinning theory for its assumptions and to develop its model. Self-administered questionnaires were distributed to the industrial SMEs owners in the Kurdistan region of Iraq. A total of 432 innovative enterprises were involved in this study, making an overall 63.9% response rate. This study utilized the partial least squares structural equation modelling (PLS-SEM) to establish the validity and reliability of the measurement model and to test the relationships. The outcomes of this study show that both absorptive capacity and entrepreneurial orientation have significant influences on technological innovation capabilities. Furthermore, the results indicate that market orientation has a partial mediating role in the nexus between absorptive capacity and technological innovation capabilities, but it has not been found to mediate the relationship between entrepreneurial orientation and technological innovation capabilities. This study offers theoretical and practical contributions for academics and professionals. The limitations of the study have been addressed and some valuable suggestions for future research work are offered.